Performance Improvement Polyvinylidene Fluoride (PVDF) Mordenite Membranes for Oil-in-Water Emulsion Separation - Brigitta Elga Kusuma Dewi; Pranoto Pranoto; Edi Pramono; Ozi Adi Saputra (ALCHEMY Jurnal Penelitian Kimia, 2024)
Improving the performance of membranes appropriate for oil-in-water separation is a global challenge. In this study, we prepared a PVDF/Mordenite (PZM) membrane and determined its properties to separate oil-in-water emulsions to address this challenge. The PVDF and PZM membranes were fabricated using the phase inversion technique and applied to separate two types of oil-in-water emulsions 1:99 (wt%), including vegetable oil and used cooking oil emulsion. PVDF polymer with DMAc solvent was added to mordenite with a concentration variation of mordenite. The addition of mordenite did not affect the increase of the β fraction on the hybrid membrane surface but could improve the membrane hydrophilicity. The addition of mordenite in the PVDF membrane has improved the characteristics of the membrane, including water flux, rejection membrane >90%, and FRR up to two times greater than a pristine PVDF membrane. Morphological analysis of the membrane confirmed an asymmetric membrane composed of finger-like and sponge-like. Combining mordenite and PVDF membrane to separate oil-in-water emulsions provides a new approach to oil wastewater treatment.